Disfungsi Keluarga: Telaah Fantasi Sedarah Melalui Teori Sistem Ekologi dan Fungsi Keluarga Dalam Islam - Syifa Lailya Wigaswanda; Hendar Riyadi; Esty Faatinisa; Nabila Julianti Rahman; Afiifah Dinda Luthfiana; Nadia Nur Padila (Yayasan Cendekia Gagayunan Indonesia, 2025)
The emergence of the online community “Fantasi Sedarah” reflects a severe form of family dysfunction, where moral values and core family functions have failed. This study aims to examine the relationship between family dysfunction and sexual deviance within this community by applying Bronfenbrenner’s ecological systems theory and the Islamic concept of family function by Khurshid Ahmad. This research uses a qualitative approach with a case study design and digital ethnography (netnography). Data were collected through observation of the online community, and news documentation. The findings reveal that the community’s existence is not only rooted in micro-level failures such as within the family but is also reinforced by exosystems like social media and a macrosystem that is permissive toward deviant content. The discussions within the group normalize deviant behaviors, indicating the collapse of the family’s moral and emotional protection roles. This study concludes that the “Fantasi Sedarah” phenomenon is a multidimensional crisis requiring collaborative responses from families, education systems, legal authorities, and digital platforms.